José Martí, Precursor of Our American Pedagogy - Wainstok, Carla (2011)
The main idea of this work is to reflect on José Martí's contributions to OurAmerican pedagogy. It is known thatthere are a lot of concrete, varied and rich experiences regarding Latin American teaching practices; however, there is a lack of reading interest in order to create our own thinking matrix. That is, the systematization of practices is fragmented and particular which hardens the interpretation of a proper account. In this essay, we move toward a Latin American pedagogy definition.